2020
DOI: 10.1021/acs.iecr.9b05729
|View full text |Cite
|
Sign up to set email alerts
|

Ethanol as a Renewable Building Block for Fuels and Chemicals

Abstract: Three factors, (i) the ethanol “blend wall”, which limits its market as a transportation fuel, (ii) advances in production efficiency, and (iii) feedstock diversification, could lead to excess ethanol at competitive prices. Those factors have already motivated a search for value-added derivatives (e.g., distillate fuels, olefins, and asymmetric amines). Siting small, low cost, flexible conversion facilities to process ethanol at or near the fermentation plant could encourage the growth of an enterprise. Decrea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
78
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 102 publications
(87 citation statements)
references
References 96 publications
0
78
0
1
Order By: Relevance
“…The presence of OH groups makes the ethanol a polar molecule. Moreover, the reactivity of the hydroxyl group permits its ready conversion into industrially significant products and intermediates via dehydration, dehydrogenation, condensation, etherification, and/or oxidation reactions [7].…”
Section: Chemistry and Types Of Bioethanol Sourcesmentioning
confidence: 99%
“…The presence of OH groups makes the ethanol a polar molecule. Moreover, the reactivity of the hydroxyl group permits its ready conversion into industrially significant products and intermediates via dehydration, dehydrogenation, condensation, etherification, and/or oxidation reactions [7].…”
Section: Chemistry and Types Of Bioethanol Sourcesmentioning
confidence: 99%
“…As discussed, the possible range of syngas-to-fuel pathways is very extensive. From this extensive list, the possible range of technologies was down-selected to an ethanol-and methanolbased pathway, as both are versatile chemicals that can be further converted into fuels, and a wide range of chemicals and products (Dagle et al 2020). As such, future studies building on this work may enable evaluation of chemical products or co-products, which can significantly improve the process economics (Dagle et al 2020).…”
Section: Selected Hydrocarbon Fuel Routes For Teamentioning
confidence: 99%
“…From this extensive list, the possible range of technologies was down-selected to an ethanol-and methanolbased pathway, as both are versatile chemicals that can be further converted into fuels, and a wide range of chemicals and products (Dagle et al 2020). As such, future studies building on this work may enable evaluation of chemical products or co-products, which can significantly improve the process economics (Dagle et al 2020). In addition, existing process models previously developed by PNNL for biomass gasification and conversion to synfuels via the methanol and ethanol-based pathways could be leveraged and adapted.…”
Section: Selected Hydrocarbon Fuel Routes For Teamentioning
confidence: 99%
“…[5] Ther eactive nature and low thermal stability of the intermediate compounds means that parallel chemistries such as dehydrogenation, dehydration, esterification, and Tishchenko reactions may occur, producing arange of products such as aldehydes,esters,alkenes,and ketones. [6] As the promoted mixed oxides catalysts typically used for these chemistries are similar in nature, [7] selective C À Cc oupling relies on the delicate balancing of catalyst characteristics and operating conditions to avoid activation of unwanted side reactions.A sp roducts,C 5+ ketones are typically only observed as minor fractions in ethanol coupling reactions.H owever,k etones are regularly generated during the formation of isobutene over ZnO-ZrO 2 catalysts,w hich proceeds through an acetone intermediate formed from acetaldehyde coupling.T he high reaction temperature leads to rapid self-condensation of acetone into diacetone alcohol that produces isobutene by decomposition, [7a,8] but appropriate modification of the catalyst and conditions to instead favor acetone coupling with acetaldehyde can offer apathway towards forming longer ketones.L iterature on ABE condensation reactions has shown that promotion of Pd is particularly suitable to selectively enable the hydrogenation of a,b-unsaturated ketones to cease the undesired reactions and improve the C 5+ ketones products. [1c, 9] Based on these previous works,am ultifunctional Pd promoted ZnO-ZrO 2 catalyst was developed to upgrade the ethanol to C 5+ ketones in ao ne-pot catalytic process.…”
Section: Introductionmentioning
confidence: 99%